2005
DOI: 10.1007/s10641-004-5564-8
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of ningu, Labeo victorianus (Pisces : Cyprinidae), in the Kagera and Sio Rivers, Uganda

Abstract: SynopsisWe investigated aspects of the reproductive biology of the cyprinid fish, Labeo victorianus, locally known as ningu, in the Kagera and Sio Rivers, Uganda. These rivers represent the last remaining refuges for this species within Uganda. L. victorianus is a highly fecund, potamodrometic fish that migrates upstream to spawn. Spawning is generally synchronised with the bimodal water level maxima observed within the rivers. There were, however, some deviations from this pattern. We caught sexually mature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…This author observed that higher values of the GSI predominated in the species that were total spawners, whereas the lower and intermediate values were more frequent in the fishes that were multiple spawners. Nevertheless, in spite of the lack of monthly samples to establish the picture frequently adopted to describe the fishes' reproductive period (Garutti, 1989;Goulart, 1994;Vazzoler, 1996;Hotos et al, 2000;Rutaisire and Booth, 2005;Vallisneris et al, 2006;Hardie et al, 2007;Allison et al, 2008), the higher frequency of mature specimens with a high GSI in August and September (short dry season) was evidence for more intensive spawning activities in these months.…”
Section: Discussionmentioning
confidence: 99%
“…This author observed that higher values of the GSI predominated in the species that were total spawners, whereas the lower and intermediate values were more frequent in the fishes that were multiple spawners. Nevertheless, in spite of the lack of monthly samples to establish the picture frequently adopted to describe the fishes' reproductive period (Garutti, 1989;Goulart, 1994;Vazzoler, 1996;Hotos et al, 2000;Rutaisire and Booth, 2005;Vallisneris et al, 2006;Hardie et al, 2007;Allison et al, 2008), the higher frequency of mature specimens with a high GSI in August and September (short dry season) was evidence for more intensive spawning activities in these months.…”
Section: Discussionmentioning
confidence: 99%
“…The logistic parameters were estimated by nonlinear minimization of a negative binomial loglikelihood of the form (Maartens and Booth 2005;Rutaisire and Booth 2005) …”
Section: Length At Sexual Maturitymentioning
confidence: 99%
“…In this case, parameter G equals 1. The logistic parameters were estimated by the non-linear minimization of a negative binomial log-likelihood of the form (Maartens and Booth, 2005;Rutaisire and Booth, 2005) ln ln ln (1 ) 1…”
Section: Length At 50% Maturity (L 50 )mentioning
confidence: 99%